Morphological influence of graphene and FeSO4 on polyaniline and application of nanocomposite towards oxygen reduction reactions in acid medium - Francklin Philips Muthukrishnan; Pavithra Bharathi Sundararajan; Akilan Murugesan (Hybrid Advances)
The aim of non-precious metal catalysts (NPMCs) is to replace expensive Pt-based catalysts for fuel cells. NPMCs require not only high oxygen reduction reaction (ORR) catalytic activity but also cheap ingredients and the facile synthetic method of the catalyst is amendable to mass production. We describe a potential catalyst for catalyzing the cathodic ORR, which is synthesized by a facile method: A graphene-polyaniline-iron nanoparticles/polyaniline-iron nanoparticles nanocomposite (Gr-PANI-Fe NPs/PANI-Fe NPs NCs) were prepared via a facile one-pot synthesis method involving chemical oxidative polymerization in acid medium. NCs are characterized for their morphology and microstructure by scanning electron microscope (SEM) with energy dispersive analysis of x-rays (EDAX), x-ray diffraction (XRD) analysis and x-ray photoelectron spectroscopy (XPS) analysis. Gr-PANI Fe NP NC and PANI-Fe NPs NC exhibited nanoflower (designated as GPF NF NC) and nanorod (designated as PF NR NC) like morphology, respectively. Herein, the synergistic influence of Gr and Fe NPs on PANI nanostructure was evaluated with analytical tools. Besides, the electrocatalytic performance of GPF NF NC/PF NR NC glassy carbon modified electrodes (GPF NF NC/PF NR NC GC-MEs) has been evaluated for their electrocatalytic performance towards oxygen reduction reaction (ORR) in acid environment. The electrocatalytic behavior is examined by the linear sweep voltammetry technique. It is found that the GPF NF NC GC-ME showed better performance when compared with PF NR NC GC-ME towards ORR. Both Gr and FeSO4 have predominant impact on the morphology of PANI chain. Such morphological influence reflects on efficiency of MEs in ORR process.